Russian Grain Exports in the Context of Regional Economic Policy - Krylatyh, Elmira Nikolaevna; Belova, Tatyana Nikolaevna (Economy of Regions, 2018)
Over the past two years, Russia has become the world leader in grain exports and intends to maintain growth rates. The authors enter into polemics with scientists who estimate the export of grain as the success of the agrarian economy. The purpose of the study is to find arguments for proving that the current model of the food market formation is erroneous. This model is based on the export of grain in combination with the import of the food with high added value. Our hypothesis is that the export of grain abroad was the result of low demand in the domestic market, which is due to the structural deformation of agricultural production. The study is based on the works of scientists in foreign trade policy (D. Ricardo, F. List, B. Ulin, S. Witte, D. Mendeleev). Statistical data, include the period before the embargo on food (2012-2014) and after it (2015-2016). In the conditions of inflation, preference was given to the indicators of the physical volume of output. The situation on the food market is complicated by a decrease in consumer demand and a fall in real incomes of the population. The imposition of an embargo on food imports reoriented imports to other countries. We propose measures of state regulation of the agro-food market: the introduction of export duties on grain and export subsidies for products with high added value. The research results can be used to develop mechanisms for regional economic policy in the agro-food sector.